Answer:
13/115.
Explanation:
Formula for the average rate of change of a function:
![A(x)=(f(b)-f(a))/(b-a)](https://img.qammunity.org/2023/formulas/mathematics/college/j9kcqten0he3ojkjy62bf6sh3rasttnvxr.png)
Say that b=6 and a=0.
Find the values that the function gives with these 2 values:
![f(6)=(2(6)-1)/(3(6)+5)=(11)/(23) \\\\f(0)=(2(0)-1)/(3(0)+5)=(-1)/(5) \\\\](https://img.qammunity.org/2023/formulas/mathematics/college/5xt6g0gxru86sm9b7uijx9nrwh527xoxbe.png)
Now we substitute these values in the formula:
![A(x)=(((11)/(23) )-((-1)/(5) ))/(6-0)](https://img.qammunity.org/2023/formulas/mathematics/college/xso5o1u02jh8pvyqyi6t1uzq4k4724rhj4.png)
Let's solve the fraction substraction:
![(11)/(23)- (-1)/(5)=(11)/(23)+ (1)/(5)=(55)/(115)+ (23)/(115)=(78)/(115)](https://img.qammunity.org/2023/formulas/mathematics/college/2kde3p1f6rhowyhwmoa2ixm0uyi0bv4vln.png)
Substitute and solve the division:
![A(x)=((78)/(115) )/(6)= (78)/(115)*(1)/(6) =(78)/(690)=(13)/(115)](https://img.qammunity.org/2023/formulas/mathematics/college/uyj5mely1drhuyj2fi0y8x8vx34c6e5a0p.png)